2018
DOI: 10.1017/s1368980018002525
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetable consumption is associated with improved mental and cognitive health in older adults from non-Western developing countries

Abstract: ObjectivesConsumption of fruits and vegetables has been shown to contribute to mental and cognitive health in older adults from Western industrialized countries. However, it is unclear whether this effect replicates in older adults from non-Western developing countries. Thus, the present study examined the contribution of fruit and vegetable consumption to mental and cognitive health in older persons from China, India, Mexico, Russia, South Africa and Ghana.DesignRepresentative cross-sectional and cross-nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 46 publications
1
19
0
1
Order By: Relevance
“…The systematic review of the observational studies analyzing the association between the intake of fruit and vegetable and mental health in adults revealed the possible beneficial influence of the indicated products. This association was studied for various aspects of mental health, ranging from general and mental well-being [35,45,49,62,68,77,82,84,94], quality of life [36,39,42,43,47,55,70], sleep quality [55], life satisfaction [50,66,82], flourishing [50], mood [50,62,68,77,81], self-efficacy [56], curiosity [68], creativity [68], optimism [91,93], self-esteem [90], stress [40,48,67,71,73,80,89,92], nervousness [82], or happiness [52,59,65,82], to anxiety [35,…”
Section: Discussionmentioning
confidence: 99%
“…The systematic review of the observational studies analyzing the association between the intake of fruit and vegetable and mental health in adults revealed the possible beneficial influence of the indicated products. This association was studied for various aspects of mental health, ranging from general and mental well-being [35,45,49,62,68,77,82,84,94], quality of life [36,39,42,43,47,55,70], sleep quality [55], life satisfaction [50,66,82], flourishing [50], mood [50,62,68,77,81], self-efficacy [56], curiosity [68], creativity [68], optimism [91,93], self-esteem [90], stress [40,48,67,71,73,80,89,92], nervousness [82], or happiness [52,59,65,82], to anxiety [35,…”
Section: Discussionmentioning
confidence: 99%
“…This study confirms that higher vegetable and fruit consumption and physical activity are protective against cognitive decline in older adults. Vegetables and fruits are rich in antioxidant vitamins and nutrients, compounds that are considered important for the protection against oxidative stress and inflammation, which, in turn, have been shown to play a role in the early pathophysiology of cognitive decline (Hajjar et al, 2018;Gehlich et al, 2019). Moreover, vegetables and fruits might affects the composition of the gut microbiota and stimulate a positive modulation of the gut-brain axis, which might be another mechanistic pathway to impact cognitive health (Pistollato et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, including these covariates could not substantially explain declines in young and middle-aged adults. Thus, further research must examine age-specific risk factors for depression that might explain these differential effects, such as problematic social media use, or changes in other lifestyle factors [3,25,26]. Another methodological explanation is that cognitive biases might have unduly influenced self-reports.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, the depression prevalence was found to be relatively constant overall. However, the authors also found a shift in the age distribution in women, with significant increases in the depression prevalence among the young age group (age [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], no significant change in the middle-aged age group (age 35-49) and a significant decrease in the old age group (age 50-65). All studies point towards the need to further study cross-temporal differences in depression, considering the whole lifespan and using multi-national samples.…”
Section: Introductionmentioning
confidence: 92%